1984
DOI: 10.1172/jci111548
|View full text |Cite
|
Sign up to set email alerts
|

Catabolism of very low density lipoproteins in experimental nephrosis.

Abstract: Ab btract. The effects of experimental nephrosis in rats, produced by puromycin aminonucleoside, include an elevation of plasma levels of all lipoprotein density classes and the appearance of high density lipoprotein (HDL) rich in apoprotein (apo) A-I and deficient in apo A-IV and apo E. The hyperlipoproteinemia is associated with an increase in hepatic synthesis of lipoproteins. The possible role of decreased very low density lipoprotein (VLDL were obtained from nonfasting animals by ultracentrifugation at d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 38 publications
2
33
0
Order By: Relevance
“…Under normal conditions, HDL binding to the SRB1 docking receptor in the liver accommodates hydrolysis and removal of its triglyceride and phospholipid contents by hepatic lipase 9 . In vitro analyses have demonstrated a marked reduction in heparin-releasable lipase activity in the livers of nephrotic rats compared to control rats 45 . Moreover, marked downregulation of hepatic lipase expression and activity in hypercholesterolaemic Imai rats with spontaneous focal segmental glomerulo sclero sis, and rats with puromycin aminoglycoside-induced nephrotic syndrome has also been reported 46,47 .…”
Section: Acquired Lcat Deficiencymentioning
confidence: 96%
“…Under normal conditions, HDL binding to the SRB1 docking receptor in the liver accommodates hydrolysis and removal of its triglyceride and phospholipid contents by hepatic lipase 9 . In vitro analyses have demonstrated a marked reduction in heparin-releasable lipase activity in the livers of nephrotic rats compared to control rats 45 . Moreover, marked downregulation of hepatic lipase expression and activity in hypercholesterolaemic Imai rats with spontaneous focal segmental glomerulo sclero sis, and rats with puromycin aminoglycoside-induced nephrotic syndrome has also been reported 46,47 .…”
Section: Acquired Lcat Deficiencymentioning
confidence: 96%
“…46 Although possible effects of 3-thiadicarboxylic acid treatment on VLDL clearance were not specifically addressed in the present study, several observations indicated that the hypolipidemic properties of 3-thiadicarboxylic acid are probably not mediated by any major effect on VLDL catabolism. First, no effect on LDL receptor activity was seen, as discussed above.…”
mentioning
confidence: 72%
“…These results raise a question about the previous concept that hyperlipidemia in nephrosis was mainly due to overproduction of lipoproteins in the liver2). It is unlikely that puromycin aminonucleoside may directly impair the liver function, so that the present results merely reflect the hepatic damages by the agent, because we used 10-14 days post-puromycin injected rats as an animals model of nephrosis, which is the similar experimental design reported by otherss, 9,11,16,19). In addition, Joven et al 28) recently reported that there was no consistant abnormal lesion in the liver of puromicin-induced nephrotic rats when observed either light or transmission electron microscopy.…”
Section: Discussionmentioning
confidence: 92%